Dynamics and Population Structure of Bali Cattle in Baito District South Konawe Regency - Oktaviani, Dea Nanda; Hafid, Harapin; Aku, Achmad Selamet (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2024)
The aim of this study was to investigate the dynamics and population structure of Bali cattle in the Baito District of South Konawe Regency. The research was conducted from December 2022 to January 2023. Sample villages/kelurahan were selected using purposive sampling, and four villages/kelurahan were identified as research locations. Respondents, totaling 20 individuals per village who owned Bali cattle, were selected using the purposive sampling method. The data collected included both primary and secondary data. The observed variables encompassed population dynamics, including the influx and outflow of cattle, and population structure, comprising male Bali cattle, calves, heifers, adult females, and female Bali cattle. The findings revealed population dynamics in Baito District, with a birth rate of 207 livestock (average 51.75), a mortality rate of 18 cattle (average 4.50), a selling rate of 58 cattle (average 14.50), and a purchase rate of 19 livestock (average 4.75). Consequently, the average livestock entering was 56.25, while the average livestock leaving was 19.25. Analyzing the population structure based on physiological status in the Baito District, adult female Bali cattle constituted 40.00%, heifers accounted for 16.58%, and female calves comprised 5.26% of the total study population. Additionally, adult males represented 18.42%, young males were at 15.00%, and male calves constituted 4.74%.